Implementation of multidisciplinary team decisions on the management of complex bone and joint infections: an observational study - Jaap L.J. Hanssen; Henrica M.J. van der Linden; Martha T. van der Beek; Robert J.P. van der Wal; Marco F. Termaat; Mark G.J. de Boer; Henk Scheper (BMC Musculoskeletal Disorders)
Abstract Background Multidisciplinary team (MDT) management of prosthetic joint infections (PJI) and other bone and joint infections (BJI) is increasingly put into practice. However, studies evaluating the performance of MDTs in this field are scarce. We aimed to assess our MDT for complex BJI by determining the implementation rate of team decisions, analyzing factors associated with non-implementation and evaluating the clinical outcome of patients in whom MDT decisions were not implemented. Methods An observational study was conducted on all patients with a PJI or other BJI of which the management was discussed during MDT meetings between 2015 and 2022 in a tertiary care academic hospital. Patient characteristics and MDT data were obtained from electronic patient records. The multidisciplinary team consisted of orthopaedic surgeons, trauma surgeons, infectious diseases specialists and clinical microbiologists. A decision was considered not implemented if the patient did not receive the management that was decided by the MDT. Factors possibly associated with non-implementation were statistically analyzed using logistic regression. Results The analysis included 1321 MDT decisions on 509 patients. The overall implementation rate of MDT decisions was 92%. Reasons for non-implementation were disagreement by the treating surgeon with the MDT regarding the optimal treatment (n = 24, 23%), patient preference for a different treatment (n = 19, 18%), new clinical information not yet available during the MDT meeting that made the physician change management (n = 17, 16%) or unknown (n = 45, 43%). Trauma surgeons were more likely to not implement an MDT decision (odds ratio 2.4, p = 0.01) The cure rate of patients who received a different surgical strategy than decided by the MDT was 33%. The cure rate was lower if a patient chose to deviate from the MDT decision (46%) than when the treating physician chose to deviate from the MDT decision (77%). Conclusion The implementation rate of decisions made by our complex BJI MDT was high. Furthermore, the current study suggests that non-implementation of MDT decisions on surgical management and non-implementation initiated by the patient lead to poor clinical outcomes. An analysis of MDT decision implementation is a useful tool to evaluate the impact of MDTs and further improve its quality.